Some aspects on health development in Cuba. - Olga Lourdes Vila Pérez (Medisur)
In the context of distribution's relationships, the correlation between development's economic and social aspects has been object of singular debates. Inside this phenomenon, the Cuban social policy, and specifically the health sector shows encouraging results and comparable with those of industrialized countries. As acknowledgment to this sector, for the achievement and maintenance of these results, this work seeks to publish some of the most significant goals reached by the Cuban health system, as well as the influence of these services in the economic growth of the country.